Radio coverage of the 1990 Malaysian general elections / Kiranjit Kaur - Kaur, Kiranjit (Faculty of Communication and Media Studies (FCMS), 1994)
Malaysia's mass media can be divided mainly into two categories i.e. government mass media and private mass media. All government mass media activities are coordinated by the Ministry of Information. The Ministry has two main divisions: the Department of Broadcasting and the Department of Information. The Ministry drew up five guidelines for government communicators and broadcasters.